Intersections of climate, security and human mobility in Honduras - Higuera Florez, Julian; Madurga Lopez, Ignacio (2024)
In the past decades Honduras has been heavily affected by fragility and different types of conflict and violence, including high homicide, femicide and crime rates, gang violence and extortion, drug trafficking, socioenvironmental conflicts and political instability. These security issues are deeply rooted in structural socioeconomic and political inequalities. High rates of poverty, unemployment, food insecurity and economic inequality as well as unequal access to natural resources are among the main challenges faced by a country ranked as one of the three least peaceful in Latin America and the Caribbean.